O Vaticano II e a opção pelo diálogo inter-religioso - Wolff, Elias (Revista eclesiástica brasileira, 2013)
Religious pluralism is an increasingly expressive reality in the present globalized society. Religions have broken barriers and original contexts, influencing the new environments and being influenced by them. There, the encounters between the creeds happen in the midst of the conflicts generated by attitudes of intolerance, prejudice and discrimination. This is not just a religious issue; it is also anthropological, sociological and ethical. We attempt to show here that the posture of the Vatican II in the plural religious world is supported by three pillars: the definite overcoming of the axiom extra ecclesiam nulla salus; the role of the religions in Christ’s salvific action; and the pastoral perspective of the inter-religious dialogue and cooperation. In a Theo-anthropological perspective, we try to understand how the only history of salvation happens in and through the history of the religions, so that whatever “particularity” may exist in one religion is not “another” history of salvation, “external” to God’s universal design that comes true in Christ.Keyword: Vatican II. Interreligious dialoge. Church. Religious pluralism.